2009
DOI: 10.1080/01421590802637966
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a national process of reforming curricula in postgraduate medical education

Abstract: Context: A national reform of the postgraduate medical education in Denmark introduced (1) Outcome-based education, (2) The CanMEDS framework of competence related to seven roles of the doctor, and (3) In-training assessment. Objectives: The purpose of the study was to evaluate the process of developing new curricula for 38 specialist training programmes. The research question was: which conditions promote and which conditions impede the process? Methods: Evaluation of the process was conducted among 76 contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 24 publications
(24 reference statements)
4
35
0
Order By: Relevance
“…The national and regional implementation activities were effective mechanisms for communication, interpersonal influence, knowledge sharing and learning, and social networking. This is consistent with previously published work on the importance of communication and interpersonal influence in innovation processes (Rogers 2003), including processes in the context of undergraduate medical education (Bland et al 2000), and PGME (Lillevang et al 2009). …”
Section: Attributes Of the Implementation Processsupporting
confidence: 90%
See 3 more Smart Citations
“…The national and regional implementation activities were effective mechanisms for communication, interpersonal influence, knowledge sharing and learning, and social networking. This is consistent with previously published work on the importance of communication and interpersonal influence in innovation processes (Rogers 2003), including processes in the context of undergraduate medical education (Bland et al 2000), and PGME (Lillevang et al 2009). …”
Section: Attributes Of the Implementation Processsupporting
confidence: 90%
“…It has been shown that such targeted support accelerates and facilitates processes of implementation (Rogers 2003). However, in a PGME curriculum reform in Denmark, educational support had in some aspects an impeding impact on the process (Lillevang et al 2009). As in the Netherlands, in Denmark, the professionals required and requested additional educational support for implementing the renewed PGME curricula.…”
Section: Regional Implementation Strategies and Educational Supportmentioning
confidence: 98%
See 2 more Smart Citations
“…Calls from society for more transparency with regard to the content and quality of medical education have been the prime drivers of the fairly recent shift to competency-based postgraduate medical education and training in many, mainly Western, countries (Maudsley et al 2000;Jones et al 2001;Leach 2001;Carraccio et al 2002;Frank 2005;Scheele et al 2008;Lillevang et al 2009). The introduction of competencybased curricula was based on the assumption that such training would provide future physicians with better preparation for the full scope of contemporary medical practice or, in the words of the Royal College of Physicians and Surgeons of Canada, would train 'better physicians' (Frank 2005).…”
Section: Introductionmentioning
confidence: 99%